Studies of ir absorption spectra of nickel oxides (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The study of infrared absorption spectra of nickel oxides is of scientific and practical interest, as these materials are widely used in industry, energy, electronics, and catalytic processes. The relevance of this work is due to the need to obtain materials with controllable physicochemical properties. The aim of the research is to determine the structural features and composition of nickel oxides, as well as to study the influence of synthesis conditions on their properties. The IR spectroscopy method makes it possible to identify the nature of chemical bonds, the oxidation state, and lattice defects, which makes it an important tool for studying NiO.
Keywords: oxides, spinels, IR spectra, decomposition, compounds